2013
DOI: 10.1590/s0001-37652013005000049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of wound healing and antimicrobial properties of aqueous extract from Bowdichia virgilioides stem barks in mice

Abstract: The decoction of the stem barks from Bowdichia virgilioides KUNTH is a folk remedy used to treat inflammatory disorders in Latin American and Brazil. In the present study, the wound healing activity of aqueous extract of the stem bark from B. virgilioides, called AEBv, was evaluated by the rate of healing by wound contraction and period of epithelization at different days post-wound using the wound excisional model. On day 9, the AEBv-treated animals exhibited significative reduction in the wound area when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…However, prolonged inflammation phase causes delaying of healing process. [16] Anti-inflamatory activity of yacon leaves extract plays a role for shorten the healing period.…”
Section: Macroscopic Evaluation Of Wound Healingmentioning
confidence: 99%
“…However, prolonged inflammation phase causes delaying of healing process. [16] Anti-inflamatory activity of yacon leaves extract plays a role for shorten the healing period.…”
Section: Macroscopic Evaluation Of Wound Healingmentioning
confidence: 99%
“…For wound healing and antimicrobial properties, a study employed by Agra et al . [ 15 ] showed that the aqueous extract from Bowdichia virgilioides stem barks can be used in mice. Jiao et al .…”
Section: Introductionmentioning
confidence: 99%
“…This delay in wound healing may be due to flavine being a disinfectant and therefore kill new immature cells while having no inherent proliferative properties. As a comparison, L. pumila is an excellent wound healing agent with proliferative properties and has inherent antimicrobial properties to prevent wound infection (Agra et al, 2013).…”
Section: Discussionmentioning
confidence: 99%